Impact of delay to surgery on survival in stage I-III colon cancer. Issue 3 (March 2020) - Grass, Fabian; Behm, Kevin T.; Duchalais, Emilie; Crippa, Jacopo; Spears, Grant M.; Harmsen, William S.; Hübner, Martin; Mathis, Kellie L.; Kelley, Scott R.; Pemberton, John H.; Dozois, Eric J.; Larson, David W.
Abstract: Purpose: To assess the impact of delay from diagnosis to curative surgery on survival in patients with non-metastatic colon cancer. Methods: National Cancer database (NCDB) analysis (2004–2013) including all consecutive patients diagnosed with stage I-III colon cancer and treated with primary elective curative surgery. Short and long delays were defined as lower and upper quartiles of time from diagnosis to treatment, respectively. Age-, sex-, race-, tumor stage and location-, adjuvant treatment-, comorbidity- and socioeconomic factors-adjusted overall survival (OS) was compared between the two groups (short vs. long delay). A multivariable Cox regression model was used to identify the independent impact of each factor on OS. Results: Time to treatment was <16 days in the short delay group (31, 171 patients) and ≥37 days in the long delay group (29, 617 patients). OS was 75.4 vs. 71.9% at 5 years and 56.6 vs. 49.7% at 10 years in short and long delay groups, respectively (both p < 0.0001). Besides demographic (comorbidities, advanced age) and pathological factors (transverse and right-vs. left-sided location, advanced tumor stage, poor differentiation, positive microscopic margins), treatment delay had a significant impact on OS (HR 1.06, 95% CI 1.05–1.07 per 14 day-delay) upon multivariable analysis. The adjusted hazard ratio for death increased continuously with delay times of longer than 30 days, to become significant after a delay of 40 days. Conclusion: This analysis using a national cancer database revealed a significant impact on OS when surgeries for resectable colon cancer were delayed beyond 40 days from time of diagnosis.